Recent advances in the synthesis of cyclic pseudopeptides. (December 2017) - Zaretsky, Serge; Yudin, Andrei K.
Abstract : Constrained peptides pose tremendous value in drug discovery. For example, owing to their large surface areas, they offer novel ways at inhibiting protein–protein interactions. As this field has grown, it has become desirable to introduce non-peptidic functionality into these rings to enable differentiated structure activity relationships and improved pharmacokinetic properties. Recent advances in the synthesis of cyclic pseudopeptides include macrocyclization through cysteine alkylation, multicomponent reactions, decarboxylative couplings, and novel stapling chemistry.